2017
DOI: 10.3389/fmars.2017.00310
|View full text |Cite
|
Sign up to set email alerts
|

Ice Algae-Produced Carbon Is Critical for Overwintering of Antarctic Krill Euphausia superba

Abstract: Antarctic krill Euphausia superba ("krill") constitute a fundamental food source for Antarctic seabirds and mammals, and a globally important fisheries resource. The future resilience of krill to climate change depends critically on the winter survival of young krill. To survive periods of extremely low production by pelagic algae during winter, krill are assumed to rely partly on carbon produced by ice algae. The true dependency on ice algae-produced carbon, however, is so far unquantified. This confounds pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 94 publications
0
71
0
1
Order By: Relevance
“…Samples of particulate organic matter (POM) from surface water and sea ice were collected to provide a baseline for BSIA. Measurements confirmed that the δ 13 C values were significantly higher in sea ice-derived carbon compared to carbon derived from the water column (t-test, t = 5.2, df = 10.9, p < 0.01; Kohlbach et al 2017). There also was no overlap between the δ 13 C values of sea-ice POM and water column phytoplankton POM, confirming that these can be recognized as distinct carbon sources (Kohlbach et al 2017).…”
Section: Bulk Stable Isotope Analysis (Bsia)mentioning
confidence: 65%
See 3 more Smart Citations
“…Samples of particulate organic matter (POM) from surface water and sea ice were collected to provide a baseline for BSIA. Measurements confirmed that the δ 13 C values were significantly higher in sea ice-derived carbon compared to carbon derived from the water column (t-test, t = 5.2, df = 10.9, p < 0.01; Kohlbach et al 2017). There also was no overlap between the δ 13 C values of sea-ice POM and water column phytoplankton POM, confirming that these can be recognized as distinct carbon sources (Kohlbach et al 2017).…”
Section: Bulk Stable Isotope Analysis (Bsia)mentioning
confidence: 65%
“…This was confirmed by the δ 13 C values, which suggested that the AC0 krill had continuous access to sea ice-associated food sources (Kohlbach et al 2017).…”
Section: Sea-ice Association Of Preymentioning
confidence: 67%
See 2 more Smart Citations
“…The lipid content of E. superba and T. macrura showed a high local variability in several studies (Pond et al 1995; Hagen et al 1996; Mayzaud et al 1998; Färber-Lorda et al 2009a; Färber-Lorda and Mayzaud 2010; Ruck et al 2014; Kohlbach et al 2017). In E. superba lipid, but also protein content, was found to be highly variable within a single population during several seasons, and the variety within a season can be greater than between seasons (Torres et al 1994; Mayzaud et al 1998; Ruck et al 2014).…”
Section: Energy Density Of Zooplankton and Nekton Speciesmentioning
confidence: 98%